TEACHING ENGLISH ON THE BASIS OF PROFESSIONAL ORIENTATION AT THE FACULTIES OF NATURAL SCIENCES AS A PEDAGOGICAL PROBLEM - Tursunboyeva Mukhlisa Anvar kizi (Journals Park Publishing, 2024)
This article focuses on the problems of students of the faculty of natural sciences in the formation of a level of professional orientation in English classes. It cites solutions to be found on this issue, with examples of a number of proposals. At the same time, the opinions of a number of researchers are studied.
Keywords: natural sciences, non-philological orientation, professional competence, knowledge and skills, professional problem, universal, specialty and specialty Sciences.